Tobacco consumption pattern and dependence in an urban slum community of Mumbai - Sodaye, Vishal; Dyavarishetty, Padmavathi V. (International Journal of Research in Medical Sciences, 2025)
Background: Globally India ranks as second highest in terms of tobacco users. As per the GATS survey, 11% of all adults smoke and 21% of all adults are using the smokeless form of tobacco. The aim of the study is to assess the level of dependence on tobacco in the urban slum population aged 18 years and above in Mumbai. Methods: A descriptive cross-sectional study amongst 100 adults aged 18 years and above, selected sequentially from the sampling frame of tobacco users in the urban slum of Mumbai. Results: Amongst the 100 respondents 63 were males and 37 were females, 48% were aged 55 years or older and only 12% were below 35 years of age. All females in the study used smokeless form of tobacco, whereas 74.6% of the males used smokeless form of tobacco. 51% respondents reported the age of initiation of tobacco as 20-24 years and 34% reported a family member using tobacco products. Less than Rs. 200 per month was being spent on purchasing tobacco products by 77% of the respondents. High dependency score in Fagerstrom Test for Nicotine Dependence (FTND) was observed in 26.3% and 51.2% of smokers and smokeless tobacco users respectively. Conclusions: In the urban slum of Mumbai, smokeless form of tobacco is more prevalent than smoke form of tobacco and is highly addictive both in males and females. Family influence played a major role in initiation of tobacco use among females as compared to males.